2019
DOI: 10.1093/asj/sjz232
|View full text |Cite
|
Sign up to set email alerts
|

Local Infiltration of Tranexamic Acid With Local Anesthetic Reduces Intraoperative Facelift Bleeding: A Preliminary Report

Abstract: Background Rebound bleeding as a result of loss of epinephrine effect is a common problem encountered during facelift surgery. Tranexamic acid (TXA) is an anti-fibrinolytic agent whose safety and efficacy in reducing bleeding are well documented. We have found that local infiltration of TXA combined with a lidocaine with epinephrine solution during facelift surgery has been effective in decreasing rebound bleeding and the time required to gain hemostasis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 40 publications
2
64
0
Order By: Relevance
“…Previous studies have shown that systemic use of TXA affects the reduction of hematoma rates in rhytidoplasty or intraoperative bleeding [5,33]. In this study, there was a statistically significant difference trend (p 0.084) in the hematoma rate in patients who had irrigation with tranexamic acid versus those who did not.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Previous studies have shown that systemic use of TXA affects the reduction of hematoma rates in rhytidoplasty or intraoperative bleeding [5,33]. In this study, there was a statistically significant difference trend (p 0.084) in the hematoma rate in patients who had irrigation with tranexamic acid versus those who did not.…”
Section: Discussionsupporting
confidence: 45%
“…We put forward that TXA due to its low cost, its safety in use, and its effectiveness in results [5,20,33] should be considered a fundamental tool in the prevention of complications in rhytidoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…One case series, 25 2 retrospective cohort studies, 26 , 27 1 prospective cohort, 28 and 1 RCT29 were identified regarding the use of TXA in facelift procedures involving 194 patients with an average age of 61.8 years. Of these patients, 94 underwent an extended deep plane facelift, 61 had a face lift with SMAS plication.…”
Section: Face Liftmentioning
confidence: 99%
“…In 2019, Couto et al 27 conducted a study on 27 patients who underwent a facelift and received a subcutaneous injection of TXA-lidocaine 0.5% solution before skin flap dissection. The time to gain hemostasis on each side before closure was prospectively measured in 23 of the 27 patients.…”
Section: Face Liftmentioning
confidence: 99%
“…Recent studies have suggested that tranexamic acid (TXA) may be beneficial in reducing facelift bleeding intraoperatively and decreasing surgical time by inhibiting fibrinolysis and clot dissolution. 15 , 16 However, evidence that it reduces hematoma rate is currently sparse. The ideal route—intravenous, topical, or subcutaneous infiltration combined with local anesthetic—remains unclear.…”
Section: Common Complicationsmentioning
confidence: 99%